Breaking Classroom Silence: Can Spider Web Help Novice Teacher? - Lilia Indriani (Universitas Muhammadiyah Semarang, 2017)
Teaching Non-Native English Speakers (NNES) the four basic skills (listening, speaking, reading, and writing) is really a big challenge for novice teachers in Asia context that see English as a foreign language. Meanwhile, an effective Foreign Language Learning Classroom (FLLC) depends upon active participation and involvement by the learners. As the novice teachers who deal with so many styles of classroom participation, creativity and innovation in fostering TEFL is really needed especially for breaking classroom silence. This study is aboutimplementingnew teachingstrategy to break the classroom silence in teaching English in a foreign language class.In line with the shift of paradigm from teacher-centered to learner-centered, Spider Web teaching strategy could create a supportive and positive classroom climate. Climate refers to the atmosphere of the classroom, and results from the nature of the relationships between the students and the teacher, and also the kinds of communication that take place between them. This study is about teaching strategy that is used by novice teacher to break the classroom silence in teaching English as a foreign language in Asia context. Moreover, he also combines it with energizers so the learning process would be fun and exciting. After all, novice teachers, like teachers everywhere, they do have responsibilities beyond classroom.